2012
DOI: 10.1186/1471-2458-12-1097
|View full text |Cite
|
Sign up to set email alerts
|

Role of condom negotiation on condom use among women of reproductive age in three districts in Tanzania

Abstract: BackgroundHIV/AIDS remains being a disease of great public health concern worldwide. In regions such as sub-Saharan Africa (SSA) where women are disproportionately infected with HIV, women are reportedly less likely capable of negotiating condom use. However, while knowledge of condom use for HIV prevention is extensive among men and women in many countries including Tanzania, evidence is limited about the role of condom negotiation on condom use among women in rural Tanzania.MethodsData originate from a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
57
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 32 publications
16
57
4
Order By: Relevance
“…Previous studies have reported such perceptions about condom use as more evident in women older than 25 years because these women believe that condom use indicates mistrust and infidelity (Crosby et al, 2013;Exavery et al, 2012). The present findings indicate misconceptions, myths, and a lack of knowledge about how STIs/HIV can be transmitted, that place Mexican heterosexual women who are housewives at risk.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…Previous studies have reported such perceptions about condom use as more evident in women older than 25 years because these women believe that condom use indicates mistrust and infidelity (Crosby et al, 2013;Exavery et al, 2012). The present findings indicate misconceptions, myths, and a lack of knowledge about how STIs/HIV can be transmitted, that place Mexican heterosexual women who are housewives at risk.…”
Section: Discussioncontrasting
confidence: 42%
“…Length of relationship was negatively correlated with condom use (Damani et al, 2009;Exavery et al, 2012;Varela Arévalo et al, 2011). This finding may reflect cultural and gender norms, such as the belief that housewives are safe in the marriage relationship, so that they do not request condom use with their partners, even when they suspect that the partner has had another sexual partner (Gómez Alvarez & Fonseca Hernández, 2012;Ragsdale, Gore-Felton, Koopman, & Seal, 2009).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Women bear the brunt of the epidemic in subSaharan Africa, and researchers at Rufiji HDSS in Tanzania found that women who had the confidence to negotiate condom use with their partners were much more likely to use condoms. The authors recommended empowering women with condom negotiation skills as a promising means of preventing infection [72]. A study at Nouna HDSS in Burkina Faso found that women who communicated with their partners about HIV were more likely to test for the virus.…”
Section: Prevention Challengesmentioning
confidence: 99%